The Cyber index : international security trends and realities (UNIDIR GenevaCH, 2013)
Serves a a snapshot of current cybersecurity activities at the national, regional and international levels, to help policymakers and diplomats understand the complexity of the arena. Seeks to elucidate some approaches towards mitigating the risks of misperceptions, in the cyber domain that threaten to elevate international tensions or perhaps even lead to conflict.
Keywords: INTERNET